Switching Markov chains for a holistic modeling of SIS unavailability. (January 2015) - Mechri, Walid; Simon, Christophe; BenOthman, Kamel
Abstract: This paper proposes a holistic approach to model the Safety Instrumented Systems (SIS). The model is based on Switching Markov Chain and integrates several parameters like Common Cause Failure, Imperfect Proof testing, partial proof testing, etc. The basic concepts of Switching Markov Chain applied to reliability analysis are introduced and a model to compute the unavailability for a case study is presented. The proposed Switching Markov Chain allows us to assess the effect of each parameter on the SIS performance. The proposed method ensures the relevance of the results. Abstract : Highlights: A holistic approach to model the unavailability safety systems using Switching Markov chains. The model integrates several parameters like probability of failure due to the test, the probability of not detecting a failure in a test. The basic concepts of the Switching Markov Chains are introduced and applied to compute the unavailability for safety systems. The proposed Switching Markov Chain allows assessing the effect of each parameter on the chemical reactor performance.